1992
DOI: 10.1007/bf00156006
|View full text |Cite
|
Sign up to set email alerts
|

Electroretinographic oscillatory potentials in diabetic retinopathy

Abstract: The oscillatory potentials of the electroretinogram in dark and light adaptation were evaluated by Fourier transform in 87 diabetics and 74 age-matched controls. The study consisted of four groups: normal control, no observable diabetic retinopathy, background diabetic retinopathy and proliferative diabetic retinopathy. A reduction in the amplitude of each oscillatory potential, the summed amplitudes, the area and the total power of the oscillatory potentials as well as delayed implicit time of each oscillator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 14 publications
4
12
0
1
Order By: Relevance
“…In agreement with findings in people with diabetes, STZ‐diabetic rats show delayed oscillatory potential implicit time (at 12 weeks control; 28 ± 0.5 versus STZ; 33 ± 0.9 ms) 80,91 and reduced (at 12 weeks control; 107 ± 7 versus STZ; 76 ± 7 mV) oscillatory potential amplitude, 80,100,101 as shown in Figure 6. Layton, Safa and Osborne 102 and Bui and coauthors 74 reported a reduction in both oscillatory potential and b‐wave amplitudes (Figure 3A), which implies that the changes in oscillatory potential may reflect losses of ON‐bipolar cell b‐wave response.…”
Section: Laboratory Evidence Linking Diabetes and Glaucomasupporting
confidence: 90%
“…In agreement with findings in people with diabetes, STZ‐diabetic rats show delayed oscillatory potential implicit time (at 12 weeks control; 28 ± 0.5 versus STZ; 33 ± 0.9 ms) 80,91 and reduced (at 12 weeks control; 107 ± 7 versus STZ; 76 ± 7 mV) oscillatory potential amplitude, 80,100,101 as shown in Figure 6. Layton, Safa and Osborne 102 and Bui and coauthors 74 reported a reduction in both oscillatory potential and b‐wave amplitudes (Figure 3A), which implies that the changes in oscillatory potential may reflect losses of ON‐bipolar cell b‐wave response.…”
Section: Laboratory Evidence Linking Diabetes and Glaucomasupporting
confidence: 90%
“…Brown [27] described the relationship of OPs to the retinal circulation. Scotopically induced OPs have been reported to be abnormal in diabetics before any microvascular or autoregulatory abnormalities can be detected [28,29]. The OPs display the earliest signs of disturbances in consequence of an increased intraocular pressure [21,30].…”
Section: Discussionmentioning
confidence: 98%
“…using the Fourier analysis for measuring the OPs, have observed reduced OP amplitude in persons with early diabetic retinopathy and suggested this assessment as a reliable quantitative method to detect diabetic retinopathy at an early stage45. Li et al 46 have also found reduced OP amplitude recorded in dark and light adaptation, in persons with background retinopathy.…”
Section: Electrophysiological Evaluation Of the Retina: Electroretinomentioning
confidence: 98%
“…Since electrophysiological abnormalities were detected in patients with unsatisfactory glycemic control, an influence of the metabolic control has been suggested31. However these data are not conclusive because other authors have not tested the relationship between FERG, OPs and metabolic control42, 45, 46, 48. In addition, Skrandies and Heinrich have observed that acutely induced hypoglycemia may influence the b‐wave of FERG50.…”
Section: Electrophysiological Evaluation Of the Retina: Electroretinomentioning
confidence: 99%